'It became quite a complex dynamic': The experiences of occupational therapy practice educators' move to digital platforms during the COVID‐19 pandemic. (7th September 2021) - Peart, Annette; Wells, Nathanael; Yu, Mong‐Lin; Brown, Ted
Abstract: Introduction: The rapid shift to digital platforms during the COVID‐19 pandemic enabled occupational therapy practice education to continue while creating unique learning opportunities for students in an environment of high demand for practice education providers. How occupational therapy practice educators experienced fieldwork supervision during this rapid redesign of service delivery is not widely understood. This study aimed to explore the experiences of practice educators who supervised occupational therapy students during the COVID‐19 pandemic in Australia. Methods: Fifteen occupational therapy practice educators participated in focus groups and individual semi‐structured interviews. Reflexive thematic analysis was used to understand the experiences of the participants and explore the barriers and facilitators to providing practice education in this context. Findings: The experiences of the occupational therapy practice educators were interpreted into three themes: (1) Opportunities lost and then created (as two subthemes); (2) The relationship between the student and practice educator (comprising subthemes of practicing self‐care and connection and support); and (3) Signing‐off of students' competencies . While digital platforms were initially viewed as limiting, they also were used to create new opportunities for student learning. Participants spoke of being mindful of their and students' wellbeing and finding ways to provide connection and support. Participants were challenged by the need to adapt how they evaluated students in the context of a pandemic. Conclusion: The findings of this study highlight the complexities of occupational therapy practice education in the rapidly shifting context of the COVID‐19 pandemic in Australia. The outcomes highlight the importance of creating new ways of using digital platforms during practice education while focussing on the relationships with students.